Reformulating ice cream to improve postprandial glucose response: an opportunity for industry to create shared value - Al-Ozairi, Ebaa; Mandani, Yousef; Alfaleh, Ghanima; Raj, Jincy; Alshammari, Shadan; Le Roux, Carel W. (Frontiers in Nutrition, 2024)
Ultra-processed foods are associated with metabolic dysfunction and driving chronic diseases. The Metabolic Matrix is a tool used to reformulate products to promote positive metabolic outcomes. The Kuwait Danish Dairy Company (KDD) has used this tool to develop a no-added-sugar products. This clinical trial tested the glycaemic response of a no-added-sugar ice cream in individuals with type 2 diabetes. The hypothesis was that the no-added-sugar ice cream would have a substantially better postprandial glycemic response than conventional ice cream in patients with type 2 diabetes. In this randomized cross over designed study, postprandial glycemic response was measured after 300 grams of no-added-sugar ice cream or normal ice cream was consumed. Despite similar composition and palatability, the postprandial responses were better with the no-added sugar ice cream, albeit that the natural sugar in the product still resulted in a marked postprandial glycaemic response. This finding emphasizes the necessity of clearly communicating to both patients and healthcare professionals that "no-added-sugar" does not equate to "zero total sugar". The path to improved metabolic health involves not only product improvement but also transparent messaging to enable informed dietary choices. Reformulation resulting in palatable no-added sugar products provides an opportunity for companies to Create Shared Value by addressing the important social problems such as obesity and type 2 diabetes, by creating scalable solutions, that are profitable. Clinical trial registration: The study was registered with ClinicalTrials.gov (Identifiers: NCT06135935).